(untitled) (Global Journal of Management and Business Research, 2024)
Retirement preparedness is a priceless process during one s tenure of employment because no individual can continue working during his or her lifetime However the low levels of financial literacy among retired Namibian police officers compromises sound retirement planning Financial stress upon retirement is particularly problematic for police officers in Namibia and this study examined the nexus between financial literacy and retirement planning The research was qualitative allowing for an in-depth exploration of the personal experiences and challenges faced by retirees There were interviews with 26 participants purposively selected from retired Namibian police officers In addition five key informants in the human resources department of the Namibian Police services then corroborated information collected Purposive-sampling enabled the research to target individuals with direct experience of retirement from the Namibian Police Service Thematic analysis indicated that upon retirement police officers found themselves in dire poverty with no sustainable income sources